Further evidence for the interaction of central and peripheral processes: the impact of double letters in writing English words - Kandel, Sonia; Peereman, Ronald; Ghimenton, Anna (Frontiers in Psychology, 2013)
Most studies on spelling processes suppose that the activation of orthographic representations is over before we start to write. The goal of the present study was to provide evidence indicating that the orthographic representations activated during spelling production interact continuously with the motor processes during movement production. We manipulated gemination to assess the influence of the orthographic properties of words on the kinematic parameters of production. Native English-speaking participants wrote words containing double letters and control words on a digitizer (e.g., DISSIPATE (Geminate) and DISGRACE (Control)). The word pairs shared the initial letters and differed on the presence of a doublet at the same position. The results revealed that latencies were shorter for Geminates than Controls, indicating that spelling processes were facilitated by the presence of a doublet in the word. Critically, the impact of letter doubling was also observed during production, with shorter letter durations (e.g., D, I, S) and intervals (DI, IS) for Geminates than Controls. Letter doubling therefore affected the whole process of word writing: from spelling recall to movement preparation and production. The spelling processes that were involved before movement initiation cascaded into processes that regulate movement execution. The activation spread onto peripheral processing until the production of the doublet was completely programmed (e.g., interval IS).